Improving organizational commitment on millennial workers in startup business - Sylvia Diana Purba; Triawan Susetyo (Jurnal Manajemen dan Pemasaran Jasa, 2021)
This research investigates the effects of passion towards organizational commitment as a mediating role to career adaptability and engagement of millennial employees in startup companies. The convenience sampling method was used to collect data from 63 millennial employees of startup companies located in Jakarta, Bogor, Depok, Tangerang, and Bekasi by distributing questionnaires via Google Form. The data collected were then analyzed using path analysis and the results showed that passion has a direct and indirect effect on organizational commitment and employee engagement. Meanwhile, career adaptability does not affect partial meditation as an intervening variable. Conversely, passion positively and significantly affects career adaptability, employee engagement, and organizational commitment.